ANALISIS PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN (STUDI PADA HOME INDUSTRI KONVEKSI SABLON INKRAFT SEMARANG) - Ridfan Trisnanda, 12.05.51.0122; Maskur, Ali (Students' Journal of Economic and Management, 2017)
This study aims to analyze empirically the effect of product quality, price perception, and quality of service to customer satisfaction in the convection Inkraft Semarang.This research was conducted at the site of convection Inkraft Semarang. The population in this study are customers who've booked on convection Inkraft Semarang. Sampling was done by using purposive sampling method, ie customers who never make purchases or bookings convection Inkraft least 2x, the customer is at least 17 years of age and the number of samples to be processed into the research data of 100 questionnaires. Data were analyzed using multiple linear regression analysis.The results showed that perceptions of price and service quality significantly influence customer satisfaction in the convection Inkraft Semarang. While the quality of the product has no effect on customer satisfaction. Keywords: product quality, perceived price, quality of service and customer satisfaction.